Effects of heat treatment on structural evolution and morphology of BaTi5O11 powder synthesized by the sol-gel method - Tangjuank S. (2014)
BaTi5O11 powder was successfully prepared and characterized by the sol-gel method. The mechanisms of BaTi5O 11 formation were studied by the fourier transform infrared spectroscopy (FTIR). The IR absorption peaks confirm the existence of a substitution reaction with the chelating reagent corresponding to different modes of vibration characteristic of the acetate group. The X-ray diffraction (XRD) results showed that the formation of single-phase monoclinic BaTi 5O11 began at 700 °C and were stable up to 1100 °C in air. The particle sizes observed from scanning electron microscopy (SEM) are about 100nm for a calcination temperature at 700 °C and 600nm at 1100 °C. © 2003 Elsevier B.V. All rights reserved.